Elastic modulus prediction of high volume fraction metal particle reinforced resin matrix composite - ZHAO Jinfeng; ZHU Fuxian; ZHUANG Bailiang; YANG Haoqing; ZHOU Yongquan (Jixie qiangdu)
In order to study the mechanical properties of high volume fraction ratio metal particle reinforced resin matrix composites, the elastic modulus of the composites was predicted based on the micromechanics theory and the meso-finite element method. Firstly, standard specimens of the composites were prepared, and their macroscopic elastic moduli were tested by uniaxial tensile experiments, and the microscopic properties were observed. Secondly, the elastic modulus of the composites was predicted by using Voigt, Reuss, Mori-Tanaka and Generalized means based on the micromechanics theory. Then, based on the microscopic particle size statistics of the specimens, the gradation of the metal particle size and its quantity were determined by using the Gaussian distribution law, and the random particle placement program was written by Python language to construct a two-dimensional representative volume element (RVE) finite element model consisting of the particles, the resin matrix, and the interface. Finally, the elastic modulus of resin matrix composites reinforced with high volume fraction metal particles was predicted by theoretical and finite element simulations. The analysis results show that the generalized means and finite element models predict the elastic modulus with less error from the experimental test results, and the elastic modulus of the composites increases with the increase of the volume fraction of the metal particles.